Adverse short-term effects of ozone on cardiovascular mortalities modified by season and temperature: a time-series study - Gao, Panjun; Wu, Yongsheng; He, Lihuan; Wang, Li; Fu, Yingbin; Chen, Jinrong; Zhang, Fengying; Krafft, Thomas; Martens, Pim (Frontiers in Public Health, 2023)
Introduction Ambient ozone pollution becomes critical in China. Conclusions on the short-term effects of ozone on cardiovascular mortality have been controversial and limited on cause-specific cardiovascular mortalities and their interactions with season and temperature. This research aimed to investigate the short-term effects of ozone and the modifications of season and temperature on cardiovascular mortality. Methods Cardiovascular death records, air pollutants, and meteorological factors in Shenzhen from 2013 to 2019 were analyzed. Daily 1-h maximum of ozone and daily maximum 8-h moving average of ozone were studied. Generalized additive models (GAMs) were applied to evaluate their associations with cardiovascular mortalities in sex and age groups. Effect modifications were assessed by stratifying season and temperature. Results Distributed lag impacts of ozone on total cardiovascular deaths and cumulative effects on mortality due to ischemic heart disease (IHD) were most significant. Population under 65 years old was most susceptible. Majority of significant effects were found in warm season, at high temperature, and at extreme heat. Ozone-associated risks in total deaths caused by hypertensive diseases reduced in warm season, while risks in IHD in males increased at high temperature. Extreme heat enhanced ozone effects on deaths caused by CVDs and IHD in the population under 65 years old. Discussion The revealed cardiovascular impacts of ozone below current national standard of air quality suggested improved standards and interventions in China. Higher temperature, particularly extreme heat, rather than warm season, could significantly enhance the adverse effects of ozone on cardiovascular mortality in population under 65 years old.